KEARIFAN LOKAL MASYARAKAT SUKU TAJIO BERBASIS MITIGASI BENCANA DI DESA KALIBURU KATA KABUPATEN DONGGALA SULAWESI TENGAH - Suci Ratika; Haliadi Haliadi; Exsa Putra; Faiz Urfan (Jurnal Samudra Geografi, 2023)
The purpose of this research is to explain the local wisdom of the Tajio people, identify forms of disaster mitigation in Kaliburu Kata Village, and analyze the role of the Tajio in maintaining local wisdom based on disaster mitigation in Kaliburu Kata Village, Sindue Tombusabora District, Donggala Regency, Central Sulawesi Province. This study used descriptive qualitative method. Collecting data using observation techniques, interviews and documentation. The results of the study show that (1) the form of local wisdom possessed by the Tajio Tribe is the tula bala tradition which contains the spirit of mutual cooperation and the vunja customary tradition as a form of gratitude for the abundant harvest. (2) The forms of disaster mitigation for the people of Kaliburu Kata Village are by looking at the signs given by nature through several animals such as forest birds, chickens, cats, and keke-keke birds. (3) The Tajio Tribe Community plays a very important role in maintaining the local wisdom based on disaster mitigation that they have and is responsible for maintaining the applicable rules and norms. This is evidenced by the behavior of people who are not active in areas that are restricted areas.